Produção de sedimentos e qualidade da água de uma microbacia hidrográfica rural - Iost, Caroline (2008)
The objective of this work was to evaluate the influence of land use in the production of sediment and water quality of the micro basin of river Mandarina micro basin, located in the city of Cascavel-PR. The liquid discharge, the suspended sediment and the physic-chemical parameters dissolved oxygen (DO), electrical conductivity, pH, temperature of the water, turbidity, color, nitrate, nitrite, total nitrogen, total phosphorus was monitoring between the months January and August 2007 at the river's main. It was determined the curve-key of the liquid discharge and discharge of suspended solid, which showed good correlation (R2 equal to 0.98 and 0.93, respectively). The results indicated a low production of sediment, average of 0,27 t dia-1 and good water quality, because the parameters have not gone beyond the limits praised by Resolution 345/05 of CONAMA for rivers, Class 2, with the exception of dissolved oxygen in some collections was below 5 mg L-1, color and total phosphorus which also exceeded the limits stipulated. Agriculture is the predominant activity in the micro basin (88%) and water courses have about 79% of the area of riparian forest required by law. It is believed that the soil management in the area of agriculture with practices such as tillage and system of terraces, as well as the presence of riparian forest in rivers, influenced for the good quality water and low production sediment on the water.